A Preliminary Study on a Novel Growth Guidance Rod System for Early-Onset Scoliosis in a Sheep Model. Issue 11 (1st June 2015) - Li, Kai; Zhao, Sheng; Wei, Xiaochun; Wang, Xiaoqiang; Sun, Jian; He, Yao; Zhen, Junping
Abstract : Study Design: An animal study with immature sheep to evaluate the effects of a multisegment growth guidance rod (MSGGR) on spine growth. Objective: To determine whether the spine of the immature sheep can still grow after MSGGR fixation. Summary of Background Data: The disadvantages for current growing rod techniques are that they can partially correct only the spinal curve and have little control to the apex of the curve. The rigidity of the spine after a growing rod procedure may also interfere with the final correction. Current systems are complex and not always affordable, especially in the developing world. Newer, more inexpensive techniques that provide 3-dimensional deformity correction while allowing normal spinal growth without surgical lengthening are still desired. Methods: The MSGGR is a rod consisting of segments. Spinal deformation in scoliosis is corrected and maintained by the rods without fusion. The system allows the growth of the fixed spinal segments. It is stable when twisted and bent but extendable when stretched. Rod extension occurs through sliding between the segments along the sockets in accordance to the growth of the spine. Ten 3-month-old immature sheep were used in this study. Dual MSGGRs were implanted to fix the lumber and low thoracic spine. Radiographs, magnetic resonance image, and computed tomographic scan of the spine were obtained to evaluate the fixation, rod extension, and spine health. Results: All of the sheep spines grew with the implants in position. The spine segments within the instruments were 12.5 ± 0.8 cm and grew by 10.9% (range: 6%–18.4%) from their original length in 4 months. None of the implants failed. No MSGGR-related complications were observed. Magnetic resonance imaging showed normal disc within the instrumented segments. Motion of the instrumented spinal segments was conserved. Conclusion: Growth guidance with this novel MSGGR allowed for continued growth in this sheep model, and repeated surgical lengthening of the system is not needed. Level of Evidence: N/A Abstract : Supplemental Digital Content is Available in the Text.A novel growth guidance technique for treatment of early-onset scoliosis was developed and evaluated on immature sheep models. Spinal segments were fixed with multisegment growth guidance rod. All of the sheep spines within the instruments grew with the implants in place during the 4-month follow-up period.